2004
DOI: 10.1002/art.20167
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation of parenteral methotrexate in active rheumatoid arthritis that has been unresponsive to conventional doses of methotrexate: A randomized, controlled trial

Abstract: Results. Sixty-four patients were eligible for entry and were switched from oral MTX to 15 mg/week IM MTX. At baseline, the mean ؎ SD DAS28 was 5.6 ؎ 0.88; after 6 weeks of IM MTX, the DAS28 had improved by a mean of 0.42 (95% confidence interval [95% CI] 0.15-0.69). At 6 weeks, 54 patients still had a DAS28 of >3.2 and were therefore eligible for randomization. By 22 weeks, 1 patient (3.7%) in each group achieved the primary outcome of a DAS28 <3.2 (95% CI for the difference between the groups ؊15% to ؉15%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 21 publications
(19 reference statements)
1
52
2
1
Order By: Relevance
“…On the contrary, our study shows that doubling the dosage of MTX from 15 mg/m 2 /week to 30 mg/m 2 /week in JIA does not lead to any further significant clinical improvement, and therefore the plateau of efficacy of MTX is reached with the parenteral administration of 15 mg/m 2 /week. Similar results have been obtained recently in a preliminary study involving adult rheumatoid arthritis (37).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, our study shows that doubling the dosage of MTX from 15 mg/m 2 /week to 30 mg/m 2 /week in JIA does not lead to any further significant clinical improvement, and therefore the plateau of efficacy of MTX is reached with the parenteral administration of 15 mg/m 2 /week. Similar results have been obtained recently in a preliminary study involving adult rheumatoid arthritis (37).…”
Section: Discussionsupporting
confidence: 91%
“…Descriptive statistics were used to characterize variability in the total intracellular MTXGlu (MTXGlu TOT ) concentrations and in the concentrations of each individual MTXGlu subtype (MTXGlu [1][2][3][4][5] Nonnormally distributed data were log-transformed when appropriate. Hierarchical clustering analyses of the data were performed as a class discovery method for subgroup analyses.…”
Section: Methodsmentioning
confidence: 99%
“…There was 40-fold interindividual Table 2). Analyses of correlations of the individual substrate concentrations of MTXGlu [1][2][3][4][5] with the MTXGlu TOT concentration revealed that the interindividual variability in the concentration of MTXGlu 3 correlated best with that of MTXGlu TOT (r ϭ 0.96, P Ͻ 0.0001).…”
Section: Demographic Characteristics Of the Patientsmentioning
confidence: 99%
See 2 more Smart Citations